2015
DOI: 10.1007/s12035-015-9326-8
|View full text |Cite
|
Sign up to set email alerts
|

Loss of GSK-3 Causes Abnormal Astrogenesis and Behavior in Mice

Abstract: Altered activity of glycogen synthase kinase-3 (GSK-3) is associated with psychiatric diseases and neurodegenerative diseases. GSK-3 is a key regulator in multiple aspects of neuronal differentiation in the brain. However, little is known about the role of GSK-3 in astrocyte development. To examine the role of GSK-3 in astrocytes, we generated a conditional knockout mouse using a GFAP-cre driver, in which the GSK-3 alpha and beta genes are deleted in astrocytes. We found that GFAP-cre-mediated GSK-3 deletion l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 68 publications
0
40
0
Order By: Relevance
“…68,69 In both studies, mice survived and there were no reported reductions in lifespan. Kim et al, 68 investigated the consequences of combined GSK-3α and GSK-3β deletion in neural progenitor cells.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…68,69 In both studies, mice survived and there were no reported reductions in lifespan. Kim et al, 68 investigated the consequences of combined GSK-3α and GSK-3β deletion in neural progenitor cells.…”
Section: Discussionmentioning
confidence: 91%
“…These mice showed massive increases in neural progenitor cell proliferation without enhanced apoptosis when compared to controls. Jung et al, 69 generated a conditional knockout mouse, in which GSK-3α and GSK-3β were deleted in astrocytes. Astrocyte specific GSK-3-DKO mice exhibited anxiety and altered social behavior with no effect on the lifespan.…”
Section: Discussionmentioning
confidence: 99%
“…64, 65 DNA constructs were transfected into attached cells using lipofectamine (Thermo Fisher Scientific Inc., Waltham, MA, USA) according to the manufacturer's protocol.…”
Section: Methodsmentioning
confidence: 99%
“…Stereological analysis of immunostained cells was performed by analyzing 1-in-6 series of 40mm coronal sections (240-mm apart). 55 The LC3 puncta numbers were assessed using ImageJ software (NIH). Immunostained sections were imaged by confocal microscopy with a 40X objective.…”
Section: Morphometrymentioning
confidence: 99%
“…BrdU injection and cell cycle analysis were performed as described previously. 55,56 Intraperitoneal injection of BrdU (20mg per kg body weight) was performed into pregnant mice at E13.5-15.5. For the analysis of cell cycle re-entry, BrdU was administered to control (Mtor loxP/C ; Dlx5/6-CIE or Mtor loxP/C ; Nkx2-1-Cre) and knockout (mtor loxP/loxP ; Dlx5/6-CIE or mtor-loxP/loxP ; Nkx2.1-Cre) mice for 24 h. Brains were fixed with 4% paraformaldehyde, sliced, and immunostained with antibodies to BrdU and MKI67.…”
Section: Brdu Administration and Cell Cycle Analysismentioning
confidence: 99%